KEMAMPUAN LITERASI MATEMATIKA SISWA SEKOLAH DASAR DITINJAU DARI GAYA BELAJAR - Ahyansyah Ahyansyah (Prosiding Seminar Nasional Lembaga Penelitian Dan Pendidikan (LPP) Mandala)
The purpose of this study was to study the mathematics literacy skills of elementary school students in terms of learning styles. One indicator of mathematics literacy ability can be seen from the ability to solve problems in everyday life in terms of the problems done by students using the steps of Blum & Leiss mathematical modeling. The study uses qualitative type of research conducted at SDN Sumbersari 2 class V Malang. The subjects of this study were 3 students who had visual, audio and kinesthetic learning styles from 17 students. The research instrument was a learning style questionnaire, test questions and analyzed using the Milles and Hubberman models (data reduction, data presentation, verification and decision making).The results of data analysis show that students who have a visual learning style have low literacy math skills. It is characterized by students who are unable to solve problems, simplify problems, turn problems into mathematical models, solve problems, fix real problems, check results and solve results. Students who have audio learning styles have moderate literacy math skills. It is characterized by students being able to explain the form and mathematics of problems correctly, being able to solve problems with mathematical models and working on mathematical problems, being able to solve problems by solving problems according to problems, checking results and producing results. But students are not able to answer unapproved questions that are recognized and questions that cannot be asked in problems, this shows that students are not able to answer problems and simplify problems. Students who have kinesthetic learning styles have low literacy math skills. It is characterized by students who are unable to solve problems, simplify problems, turn problems into mathematical models, solve mathematical problems, fix real problems, check results and activate results